Endovascular Treatment of Very Elderly Patients Aged ≥90 With Acute Ischemic Stroke. Issue 5 (3rd March 2020) - Meyer, Lukas; Alexandrou, Maria; Flottmann, Fabian; Deb‐Chatterji, Milani; Abdullayev, Nuran; Maus, Volker; Politi, Maria; Bernkopf, Kathleen; Roth, Christian; Kastrup, Andreas; Hanning, Uta; Brekenfeld, Caspar; et al.
Abstract : Background: Patients aged ≥90 were excluded or under‐represented in past thrombectomy trials; thus, uncertainty remains whether treatment benefits can be expected regardless of age. This study investigates outcome and safety of thrombectomy in nonagenarians to improve decision making in a real‐world setting. Methods and Results: All currently available data of patients aged ≥90 enrolled in the GSR‐ET (German Stroke Registry–Endovascular Treatment) were combined with a smaller cohort from 3 tertiary stroke centers. Baseline characteristics, procedural (Thrombolysis in Cerebral Infarction scale) and functional outcomes (modified Rankin Scale; mRS), as well as complications (symptomatic intracranial hemorrhage, serious adverse events; SAEs) were analyzed. Good functional outcome was defined as mRS ≤3 at 90‐days. 203 patients with anterior circulation stroke and prestroke mRS ≤3 were included. The rate of successful recanalization (Thrombolysis in Cerebral Infarction scale ≥2b) was 75.9% (154/203). Good functional outcome (mRS ≤3) was observed in 21.6% (41 of 193) at 90‐days. In‐hospital mortality was 27.1% (55 of 203) and increased significantly at 90 days to 48.9% (93 of 190; P <0.001). Symptomatic intracranial hemorrhage occurred in 3% (6 of 203) of patients. Logistic regression analysis identified Alberta Stroke Program Early CT Score (adjusted odds ratio, 1.93; 95% CI, 1.01–3.70; P =0.046) and initial National Institute of Health Stroke Scale (adjusted odds ratio, 0.85; 95% CI, 0.76–0.97; P =0.014) as independent predictors for good outcome. Patients with successful recanalization had a significant ( P =0.001) shift of mRS distribution with higher rates of good functional outcomes (23.8% [34 of 143] versus 14.9% [7 of 47]) and lower mortality at 90‐days (46.8% [67 of 143] versus 55.3% [26 of 47]). Conclusions: Despite high mortality and less frequent favorable outcome, our data suggest that thrombectomy is still effective and safe for nonagenarians. Decision making for thrombectomy in patients aged ≥90 should be based on a case‐by‐case basis with regard to initial National Institute of Health Stroke Scale and Alberta Stroke Program Early CT Score.